The role of radiation therapy in renal cancer - Pęczkowski, Piotr (Contemporary Oncology/Współczesna Onkologia, 2007)
Adjuvant radiation therapy (RT) in locally advanced renal cell carcinoma is a not standard treatment. Postoperative RT should be considered in patients with high risk of local recurrence: micro- or macroscopic nonradical resection, infiltration of pararenal fat. Conformal (3D) RT is recommended for sparing organs at risk and for precise total dose delivery. Recommended total dose is 45-50 Gy in 1.8-2 Gy fractions to the renal bed and regional lymph nodes. The toxicity of this schedule is acceptable. Preoperative RT may be applied in unresectable tumours. In these cases, 45 Gy of total dose can be considered. Palliative RT in patients with generalized metastatic disease requires single high dose fractions 6-10 Gy or lower dose fractions to a total dose of 20-40 Gy. The subjective or objective response rate is above 50%. Patients with limited metastatic disease have a possibility of long survival. The RT dose for solitary metastases is most commonly in the range 45-50 Gy in 1.8-2 Gy per fraction.